KIDNEY DYSFUNCTION IN CHRONIC HEART FAILURE - Vafoyeva Nigora Abrorovna (Journal of new century innovations, 2024)
The aim of the study was of the importance of impaired renal function in heart failure. Material and methods. 42 patients who received inpatient treatment in 2017–FC II–IV, complicated by FC II —III CHF were examined. Results. Urea levels and creatinine values (98.80±11.67 mmol/l) in both groups of the examined did not exceed normal values. Before the start of treatment, the level of Cystatin-C was 1.43 ± 0.06 mg / l in the main group of patients. In the control group, this indicator was 0.83 ± 0.01 mg / l. It was reported that the content of cystatin-C in the main group was 1.7 times higher than in the control group. After complex treatment, these values were 0.6 ± 0.01 mg / l in the main group and 0.81 ± 0.01 mg / l in the control group, respectively.